Nursing and people from other cultures - Isabel Gentil García (Universidad de Alicante, 2012)
Nursing, profession specialized in caring for people, faces in these moments the fact of having to care for people from other cultures. Sometimes only negative aspects from them are perceived and often without even being conscious of such perception. Thus, the aim of this work is to motivate reflection and critical thought on the problem of working with stereotypes of others. Hope is placed on mutual respect based on previous knowledge.